Neuroprotective Effect of Salvianolic Acid A against Diabetic Peripheral Neuropathy through Modulation of Nrf2. (27th February 2020) - Xu, Chunyang; Hou, Biyu; He, Ping; Ma, Peng; Yang, Xinyu; Yang, Xiuying; Zhang, Li; Qiang, Guifen; Li, Wenlan; Du, Guanhua
Abstract : Oxidative stress has been recognized as the contributor to diabetic peripheral neuropathy (DPN). Antioxidant strategies have been most widely explored; nevertheless, whether antioxidants alone prevent DPN still remains inconclusive. In the present study, we established an in vitro DPN cell model for drug screening using Schwann RSC96 cells under high glucose (HG) stimulation, and we found that salvianolic acid A (SalA) mitigated HG-induced injury evidenced by cell viability and myelination. Mechanistically, SalA exhibited strong antioxidative effects by inhibiting 1, 1-diphenyl-2-picrylhydrazyl (DPPH) and reducing reactive oxygen species (ROS), malondialdehyde (MDA), and oxidized glutathione (GSSG) content, as well as upregulating antioxidative enzyme mRNA expression. In addition, SalA significantly extenuated neuroinflammation with downregulated inflammatory factor mRNA expression. Furthermore, SalA improved the mitochondrial function of HG-injured Schwann cells by scavenging mitochondrial ROS, decreasing mitochondrial membrane potential (MMP), and enhancing ATP production, as well as upregulating oxidative phosphorylation gene expression. More importantly, we identified nuclear factor-E2-related factor 2 (Nrf2) as the upstream regulator which mediated protective effects of SalA on DPN. SalA directly bound to the Kelch domain of Kelch-like ECH-associated protein 1 (Keap1) and thus disrupted the interaction of Nrf2 and Keap1 predicted by LibDock of Discovery Studio. Additionally, SalA significantly inhibited Nrf2 promoter activity and downregulated Nrf2 mRNA expression but without affecting Nrf2 protein expression. Interestingly, SalA upregulated the nuclear Nrf2 expression and promoted Nrf2 nuclear translocation by high content screening assay, which was confirmed to be involved in its antiglucotoxicity effect by the knockdown of Nrf2 in RSC96 cells. In KK-Ay mice, we demonstrated that SalA could effectively improve the abnormal glucose and lipid metabolism and significantly protect against DPN by increasing the mechanical withdrawal threshold and sciatic nerve conduction velocity and restoring the ultrastructural impairment of the injured sciatic nerve induced by diabetes. Hence, SalA protected against DPN by antioxidative stress, attenuating neuroinflammation, and improving mitochondrial function via Nrf2. SalA may be prospective therapeutics for treating DPN.